Morphology of the digestive tract of the Whitemouth croaker Micropogonias furnieri (Desmarest, 1823) (Perciformes: Sciaenidae). (8th February 2016) - Andrade, Isabel M.; Guimarães, Juliana P.; Rotundo, Matheus M.; Mari, Renata B.
Abstract: Studies have shown the feeding diversity of teleostean fish, which is conditioned by environmental characteristics or the biology of the different species. Analysis on the morphology of the digestive system (DS) of fish made it possible for researchers to know the food regimen of several species at different stages of life. On the other hand, it is known that food habits may lead to morphological changes in the DS the same way that different food habits may be imposed by morphological limitations of this system. Among the species of greater commercial importance in Brazil, Micropogonias furnieri is highly representative of fish in south‐eastern Brazil. Therefore, the objective of this study was to analyse the morphology of the DS of M. furnieri . Results on the morphology of the DS observed in this study were similar to the patterns determined for the morphology of teleostean fish. In this study, it was observed that the DS of the Whitemouth croaker is directly related with the shape of the peritoneal cavity; these fish showed oesophagus, stomach, pyloric caeca and intestines. The pyloric caeca showed morphological adaptations in relation to sexual maturation, with well‐developed caeca found in sexually mature animals.